THE INFLUENCE OF DEMOCRATIC LEADERSHIP STYLE, WORK DISCIPLINE AND INCENTIVES ON EMPLOYEE PERFORMANCE AT PT MULTI BINTANG INDONESIA TBK - Wahyudi, Agus; Hasan, Muh; Kusnaedi, Elsa Mayori (Universitas Muhammadiyah Tangerang, 2025)
The purpose of this study is to determine the influence of Democratic Leadership Style, Work Discipline and Incentives on Employee Performance at PT Multi Bintang Indonesia Tbk. Sampling was 110 people. The results of the study showed that partially, the perception of democratic leadership style had a positive and significant effect on employee performance, which was shown by the t-value of the t-count > t table (3.882 >1.982) and the significance of 0.001. For the variable of work discipline partially and significantly having a positive and significant effect on employee performance, it is shown by the t-value calculated > t table (9.609 > 1.982) and the significance of 0.001. And for the partial and significant incentive variables that have a positive and significant effect on employee performance, it is shown by the t-value calculated > t table (7.856 > 1.982) and the significance of 0.001. Simultaneously positive and significant effects are shown by the F value of the F calculation > F table (40.972 > 3.08) and the significance of 0.001.